2016
DOI: 10.1159/000443893
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Opportunities for Caffeine and A<sub>2A</sub> Receptor Antagonists in Retinal Diseases

Abstract: Caffeine, the major component of coffee, is the most consumed psychostimulant in the world. Caffeine is an adenosine analog and acts as a nonselective adenosine receptor antagonist. The majority of the effects of caffeine are mainly mediated by the blockade of adenosine receptors, and the proved neuroprotective effects of caffeine in brain disorders have been mimicked by the blockade of adenosine A2A receptor (A2AR). A growing body of evidence demonstrates that microglia-mediated neuroinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 97 publications
(100 reference statements)
0
27
0
Order By: Relevance
“…The blockade of A 2A R confers neuroprotection in several models of neurodegeneration, including in the retina (Boia et al, ; Boia et al, ; Cunha, ; Gomes, Kaster, Tome, Agostinho, & Cunha, ; Gyoneva et al, ; Liu et al, ; Madeira, Boia, et al, ; Madeira, Elvas, et al, ). One of the mechanisms that may explain the protective properties of A 2A R antagonists is the control of microglia‐mediated neuroinflammation (Cunha, ; Gomes et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blockade of A 2A R confers neuroprotection in several models of neurodegeneration, including in the retina (Boia et al, ; Boia et al, ; Cunha, ; Gomes, Kaster, Tome, Agostinho, & Cunha, ; Gyoneva et al, ; Liu et al, ; Madeira, Boia, et al, ; Madeira, Elvas, et al, ). One of the mechanisms that may explain the protective properties of A 2A R antagonists is the control of microglia‐mediated neuroinflammation (Cunha, ; Gomes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine is a neuromodulator in the central nervous system acting through the activation of four receptors, A 1 , A 2A , A 2B , and A 3 . We demonstrated that the blockade of adenosine A 2A receptor (A 2A R) confers neuroprotection to the retina in glaucoma models through the control of microglia responsiveness (Boia et al, ; Boia, Ambrósio, & Santiago, ; Madeira et al, ; Madeira, Elvas, et al, ; Santiago et al, ). However, the specific role of microglial cells was not addressed, as well as the impact of A 2A R blockade in microglial cells in the context of glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of caffeine to ocular tissues have also been reported, like the prevention of diabetic cataract in galactose-fed animals and reduction of corneal thickness43. The effects of consumption of caffeine in IOP are not yet clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression increases in microglia in models of glaucoma [78,79], and A 2A R antagonists were shown to confer protection to retinal neurons, including RGCs, through the control of microglia reactivity [78,79,228]. Caffeine, a non-selective adenosine antagonist, also protects RGCs by hampering microglial cell response and controlling the neuroinflammatory environment in models of transient retinal ischemia and ocular hypertension [230,234,235]. KW6002, another A 2A R antagonist with good oral bioavailability, confers protection to the retina, including RGCs, through the control of microglia-mediated neuroinflammation [234].…”
Section: Glia-mediated Neuroprotectionmentioning
confidence: 99%